STEAP4 with copper reductase activity suppresses tumorigenesis by regulating the cell cycle in hepatocellular carcinoma cells - Ting Yang; Minhong Zou; Yujie Xie; Yong Zhang; Kun Wang; Shihai Jiang; Qiong Zou (Cell Division)
Abstract Background Abnormal expression of six-transmembrane epithelial antigen of prostate 4 (STEAP4) has been implicated in the carcinogenesis of hepatocellular carcinoma (HCC). However, the biological role and regulatory mechanisms of STEAP4 in HCC remain unclear. Methods and Results Here, we analyzed STEAP4 expression levels and differentially expressed genes (DEGs) between STEAP4 high- and low-expression groups using multiple databases. Proliferation assays, 5-ethynyl-2’-deoxyuridine (EdU) assays, propidium iodide (PI) flow cytometry, and colony formation assays were conducted to assess the effects of STEAP4 on HCC cell proliferation, cell cycle progression, and clonogenic capacity. STEAP4 was downregulated in HCC tumor tissues, with lower expression associated with poorer overall survival (OS) and disease-free survival (DFS) in patients. Functional network analysis suggested that STEAP4 regulates cell cycle signaling, with tumor sections showing a negative correlation between STEAP4 and cell cycle proteins. Overexpression of STEAP4, combined with non-cytotoxic copper exposure in the HepG2 cell line, reduced proliferation and clonogenicity, induced cell cycle arrest, and downregulated the mRNA and protein levels of cell cycle-regulating genes. A predictive model based on STEAP4 and cell cycle gene demonstrated prognostic value in HCC patients. Conclusions Our results lay a foundation for further study of the cell cycle regulatory role of STEAP4 with Cu2+ reductase activity in HCC, indicating that STEAP4 may be a promising therapeutic target for HCC.